IMPLEMENTING SENSE-BASED STRATEGY IN TEACHING VOCABULARY TO THE SEVENTH GRADE STUDENTS OF SMP NEGERI 33 MAKASSAR - Budiarti Putri Uleng (Universitas Andi Djemma, 2019)
The objective of this research was to find out whether or not Sense-Based Strategy significantly enriched the students’vocabulary masteryin terms of meaning, spelling, pronunciation, and usage.This research employed quasi-experimentaldesign.The population of this research was the seventh-grade students of SMP Negeri 33 Makassar, which consisted of ten classes in 2013/2014 academic year. The total number of population was 300 students. The researcher used a cluster random sampling technique to take the sample. Therefore, the sample of this research consisted of one class asexperimental group and one class as control group. The samples of each class were 30 students.The research data was collected by using vocabulary test to get the students’ vocabulary achievement in terms ofmeaning, spelling, pronunciationand usage, which were analyzed by descriptive and inferential statistics through SPSS version 20 for windows program. The findings of the research revealed that the students’ result of posttest of the experimental group and the students’ result of posttest of the control group were different by the mean score 67.69 > 48.50. Besides that, the mean score of experimental group in term of meaning in posttest was 74.07, the mean score of experimental group in term of spelling in posttest was 66.03, the mean score of experimental group in term of pronunciation in posttest was 59.67, and the mean score of experimental group in term of usage in posttest was 71.00. Therefore, the findings showed that the “meaning” aspect was higher than the three other aspects. In addition, the difference of both scores was statistically significant based on the t-test value at significant level 0.05 in which the probability value was lower than the significant level (0.00 < 0.05). Therefore, H1 was accepted and H0 was rejected. Furthermore, it can be concluded that implementing the Sense-Based strategy in teaching vocabulary was significant andeffective to enrich the students’ vocabulary in terms of meaning,spelling, pronunciation and usage.